Robust reconstruction of Wyner-Ziv frame for no-feedback distributed video coding - Hao QIN; Xue-lu PENG; Bin SONG; Hai-hua LIU (Tongxin xuebao)
In no-feedback distributed video coding,a robust reconstruction algorithm for Wyner-Ziv frame was proposed.To avoid the video quality degradation caused by the bit plane decoding errors,DC coefficients and AC coefficients were reconstructed with different methods.In particular,for each failure decoded quantized DC coefficient,with the help of the correlation information from the encoder,the algorithm was able to adaptively adjust the contribution of the quantized side information and the decoded quantized DC coefficient to the reconstruction.Simulation results show that compared with the MMSE (minimum mean square error) algorithm,the proposed method can increase the average PSNR (peak signal-to-noise ratio) of reconstructed video greatly,and also yield significant improvement of the subjective video quality.